2019
DOI: 10.1111/petr.13414
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation use in the first 24 hours following pediatric heart transplantation: Incidence, risk factors, and outcomes

Abstract: Primary graft dysfunction following HTx is associated with significant morbidity and mortality. This study aimed to assess the incidence of, risk factors for, and outcomes of children requiring ECMO within 24 hours of HTx. This study utilized a linked PHIS/SRTR database of pediatric HTx recipients (2002‐2016). Post‐HTx ECMO was identified using inpatient billing data. Logistic regression assessed risk factors for post‐HTx ECMO. Kaplan‐Meier analyses assessed in‐hospital mortality and post‐discharge survival. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Race and/or ethnicity was the primary study aim in five citations (13%). No statistical difference or mixed results were observed in 25 (64%) of studies (51, 52, 135–147). Studies with cardiac disease, arrest, transplant, or shock observed patients from diverse backgrounds having lower ECMO use in seven (28, 31, 129, 148–151) versus higher ECMO use in three (26, 89, 152).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Race and/or ethnicity was the primary study aim in five citations (13%). No statistical difference or mixed results were observed in 25 (64%) of studies (51, 52, 135–147). Studies with cardiac disease, arrest, transplant, or shock observed patients from diverse backgrounds having lower ECMO use in seven (28, 31, 129, 148–151) versus higher ECMO use in three (26, 89, 152).…”
Section: Resultsmentioning
confidence: 86%
“…Categories delineating race or ethnicity varied markedly. Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“…This includes support in the immediate post‐transplant period and “rescue” therapy for patients with recurrent heart failure. Extracorporeal membrane oxygenation (ECMO) remains a standard modality of support for intraoperative concerns and for acute decompensation in the immediate post‐transplant period 1–4 . However, ventricular assist devices (VADs) of both a pulsatile and continuous flow nature have been used with increasing success in transplant patients for longer durations of support 1 …”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation (ECMO) remains a standard modality of support for intraoperative concerns and for acute decompensation in the immediate post-transplant period. [1][2][3][4] However, ventricular assist devices (VADs) of both a pulsatile and continuous flow nature have been used with increasing success in transplant patients for longer durations of support. 1 Reported outcomes for post-transplant MCS have mostly focused on primary graft failure with one of the earliest reports in this patient population coming from Great Ormond Street where 10 of 129 posttransplant patients developed primary graft failure requiring mechanical support (six ECMO, four right ventricular assist device [RVAD] with two transitioned to ECMO) with 60% survival to discharge.…”
Section: Post-transplant Mechanical Circulatory Support Outcomesmentioning
confidence: 99%
“…The patients who went on VA ECMO were younger, weighed less, and had longer ischemic times compared to patients who did not need VA ECMO and decreasing survival with duration of cannulation. A similar study by Godown et al using a linked PHIS/SRTR database of pediatric heart transplant recipients reported that 7.9% required VA ECMO after transplant, of whom 85.3% were decannulated and 87.4% survived to hospital discharge [ 72 ]. The risk factors identified in those requiring VA ECMO support included younger age, congenital heart disease, VA ECMO prior to transplant, mechanical ventilation prior 74to transplant, decreased estimated creatinine clearance, and ischemic time greater than 4 h. The long-term survival in these patients was no different compared to patients who did not require ECMO support.…”
Section: Surgical Indications For Va Ecmomentioning
confidence: 99%